URGENSI PELATIHAN MEDIA SOSIAL BAGI PENINGKATAN KOMPETENSI PEGAWAI BIDANG KEHUMASAN: STUDI KASUS LEMHANNAS RI - Boy Anugerah; Yatik Wulandari (Jurnal Ranah Komunikasi, 2021)
In this globalization era, the use of social media is very massive, both by private companies and governmental institutions. Social media is used as an instrument to facilitate communication between institutions and the public, inform the activities of organizations to be well-known by the public, and strengthen public awareness towards the existence of an organization that uses social media. Nevertheless, the use of social media also causes negative impacts, such as the existence of hoaxes and hate speeches, radicalism and terrorism propagandas, and the increasing number of organized crimes. Therefore, it is a need for organization, particularly governmental institutions, to have reliable public relations officers that can operate social media to support the productivity, both for individual and organization, as well as to minimize the negative sides caused by the social media. This research aims to recommend a kind of social media training that is needed to enhance the competencies of public relations officers. This research used the qualitative descriptive approach. The data were collected through a desk research and case study method. The results of the research show that social media training is really needed to enhance the competencies of public relation officers in governmental institutions which are not sufficient enough.